Fluorinated carboxylate ester-based electrolyte for lithium ion batteries operated at low temperature. Issue 67 (21st July 2020) - Yang, Yang; Li, Panlong; Wang, Nan; Fang, Zhong; Wang, Congxiao; Dong, Xiaoli; Xia, Yongyao
Abstract : A novel fluorinated electrolyte is formulated with low freezing point and solvation energy, realizing high performance batteries that operate at low temperatures. Abstract : A well-formulated electrolyte is proposed based on a fluorinated carboxylate ester solvent, which shows a wide electrochemical window (0–4.73 V, vs. Li + /Li), low solvation energy (10.05 kJ mol −1 ) and ability to maintain a liquid state at temperatures as low as −120 °C. This electrolyte produced batteries with superior electrochemical performance at low temperatures relative to carbonate-based electrolytes.